ANASLISIS KINERJA KEUANGAN DAN KEMANDIRIAN DAERAH KABUPATEN MOROWALI - Yusuf, Sitti Khalilah (Fakultas Ekonomi Universitas Tadulako, 2015)
Analysis of Financial Performance and Regional Independence of Morowali District. In the implementation of regional autonomy, the district government is required to be able to finance its own governance. This indicates that local governments have greater responsibilities in managing their finances and increasing their level of regional autonomy. In this regard, it is necessary to conduct performance appraisal and financial capacity of local government to know the development of financial management every year. This research uses descriptive quantitative research type using ratio analysis tool. The results of the analysis show that the Financial Performance of Morowali District Government is seen from (1) Effectiveness Ratio of PAD effectiveness of financial performance of Morowali Regency can be categorized as Not Effective (2) Ratio of Financial Efficiency of Region can categorize Less Efficient (3) Economic Ratio can be categorized economically (4) Regional Financial Independence can be said to be very low with an instructive relationship pattern.